Answer:
[tex]\displaystyle \frac{4}{3}[/tex]
Step-by-step explanation:
[tex]\displaystyle 3y - 4x + 3 = 0 → 3y - 4x = -3 → 3y = 4x - 3 \\ \\ y = 1\frac{1}{3}x - 1[/tex]
When converted to Slope-Intercept Form, it is alot easier to determine the rate of change [slope] of the function because [tex]\displaystyle b[/tex] is the y-intercept, and the slope is represented by [tex]\displaystyle m,[/tex] which in this case is [tex]\displaystyle 1\frac{1}{3}, or\: \frac{4}{3}.[/tex]
I am joyous to assist you at any time.